Arteriographic examination of the thyroid gland: its anatomoclinical and histopathological correlation - Gary, R; Azambuja, N; Ravera, J J; Pedemonte, O; Acosta Ferreira, W (Cirugía del Uruguay, 2020)
Data are presented on the angiographic exploration of thyroid and are correlated with certain clinical, anatomical and histological information